Methicillin‐susceptible Staphylococcus aureus clonal complex 398: high prevalence and geographical heterogeneity in bone and joint infection and nasal carriage. (6th March 2014) - Valour, F.; Tasse, J.; Trouillet‐Assant, S.; Rasigade, J.‐P.; Lamy, B.; Chanard, E.; Verhoeven, P.; Decousser, J.‐W.; Marchandin, H.; Bès, M.; Chidiac, C.; Vandenesch, F.; et al.
Abstract The prevalence of clonal complex (CC) 398 methicillin‐susceptible Staphylococcus aureus (MSSA) was unexpectedly high among bone and joint infections (BJIs) and nasal‐colonizing isolates in France, with surprising geographical heterogeneity. With none of the major, most‐known staphylococcal virulence genes, MSSA CC398 BJI was associated with lower biological inflammatory syndrome and lower treatment failure rates.